Falling behind the PACE: lie detectors, policing and lack of foreseeability – an FOI-based study - Kotsoglou, Kyriakos N.; Oswald, Marion (Legal studies (Society of Legal Scholars), 2025)
Despite its contested scientific validity, polygraph interviewing is now an established yet opaque practice within criminal justice in England and Wales, with statute law covering polygraph use in the context of probation for released offenders. In this paper, we highlight non-statutory uses of the polygraph by police forces in England and Wales by presenting analysis of responses to freedom of information (FOI) requests. The boundaries around police polygraph use are undefined and potentially elastic. The policies disclosed state that polygraph interviewing is conducted with regard to the Police and Criminal Evidence Act 1984 (PACE) and the Human Rights Act 1998; yet it is denied that a polygraph examination is a criminal interview conducted under PACE. Furthermore, there is a significant risk that the common law may not satisfy the quality of law requirement insofar as it is insufficiently clear who will be subject to polygraph testing, why and in what circumstances. Therefore, we argue that the legal basis for the police’s use of the polygraph is inadequate and imprecise. Without openness and scrutiny regarding the extent of this use, it is difficult to see how the key human rights principle of foreseeability can protect citizens from the risk of arbitrariness.